Branched-chain amino acids modulate the proteomic profile of Trypanosoma cruzi metacyclogenesis induced by proline. - Janaina de Freitas Nascimento; Flávia Silva Damasceno; Sabrina Marsiccobetre; Francisca Natália de Luna Vitorino; Renan Weege Achjian; Julia Pinheiro Chagas da Cunha; Ariel Mariano Silber (PLoS Neglected Tropical Diseases)
Trypanosoma cruzi, the causative agent of Chagas disease, has a complex life cycle that involves triatomine insects as vectors and mammals as hosts. The differentiation of epimastigote forms into metacyclic trypomastigotes within the insect vector is crucial for the parasite's life cycle progression. Factors influencing this process, including temperature, pH, and nutritional stress, along with specific metabolite availability, play a pivotal role. Amino acids like proline, histidine, and glutamine support cell differentiation, while branched-chain amino acids (BCAAs) inhibit it. Interestingly, combining the pro-metacyclogenic amino acid proline with one of the anti-metacyclogenic BCAAs results in viable metacyclics with significantly reduced infectivity. To explore the characteristics of metacyclic parasites differentiated in the presence of BCAAs, proteomics analyses were conducted. Metacyclics obtained in triatomine artificial urine (TAU) supplemented with proline alone and in combination with leucine, isoleucine, or valine were compared. The analyses revealed differential regulation of 40 proteins in TAU-Pro-Leu, 131 in TAU-Pro-Ile, and 179 in TAU-Pro-Val, as compared to metacyclics from TAU-Pro. Among these, 22%, 11%, and 13% of the proteins were associated with metabolic processes, respectively. Notably, enzymes related to glycolysis and the tricarboxylic acid (TCA) cycle were reduced in metacyclics with Pro-BCAAs, while enzymes involved in amino acid and purine metabolic pathways were increased. Furthermore, metacyclics with Pro-Ile and Pro-Val exhibited elevated enzymes linked to lipid and redox metabolism. The results revealed five proteins that were increased and four that were decreased in common in the presence of Pro+BCAAs, indicating their possible participation in key processes related to metacyclogenesis. These findings suggest that the presence of BCAAs can reshape the metabolism of metacyclics, contributing to the observed reduction in infectivity in these parasites.